Social Life of Knowledge: Epistemological Analysis - Khairullin, Askar G.; Khairullin, Bulat A. (Journal of History Culture and Art Research, 2017)
Epistemological theory which is considered to be the fundamental philosophy of cognition process, reveals itself as a possibility justification in a supra-individual, supra-personal, impersonal, transsubjective form, taking into consideration the content of objective knowledge. Epistemology also builds a cognitive drama as a stage action to achieve it. The purpose of the article is outlined in stage-by-stage consideration of the procedure for constituting the knowledge truth by social symbolic forms and exploring the contexts for the implantation of the cognition products into the cultural frame. The leading method in constituting truth is clarified through epistemological modeling of the ontogenetic and phylogenetic context of the of symbolic categorical forms formation and is comprehended through the operational and interactive aspect. The results of epistemological analysis are as follows: 1) at the micro level, the truth is positioned in the conceptual grid as "pragmatic coherence"; 2) at the macro level, truth is positioned in the conceptual grid as "practical correspondence"; 3) at the mega level, truth is positioned not as a process, but as an accomplished present state: the subject is absorbed not in searching, but staying in the truth. The significance of the research results seems to be that the driving force of mental activity is a constructive combination. Cognitive morphogenesis is carried out as a free combination of symbolic forms, governed by the rules of experimenting on own resources, the result of which is the development of the individual spiritual world. The lever is the logic of "the generation of meanings through the discrimination of meanings," which triggers autonomous autocatalytic processes.